Delivery-room and NICU admission temperatures in preterm infants <32 weeks at a tertiary centre in Saudi Arabia: associations with mortality and morbidity - Ali, Kamal; Alrahili, Mohanned; Halabi, Shaimaa; Almahdi, Mohamed; Alrsheedi, Seham; Alessa, Amenah; Almuqati, Rana; Aljarbou, Talal; Alsenani, Mesaed; Mandurah, Abdulrahman; Alamer, Faisal; Altuwaym, Abdulrahman; et al. (Frontiers in Pediatrics, 2025)
BackgroundDespite implementation of thermal protection protocols, hypothermia remains common in preterm infants. The relative impact of hypothermia occurring in the delivery room (DR) vs. at NICU admission on neonatal outcomes remains insufficiently reported.ObjectiveTo evaluate the association between hypothermia at two key time points—immediately after birth in the DR and upon admission to the NICU—and neonatal mortality and major morbidities in infants born at less than 32 weeks’ gestation.MethodsThis retrospective cohort included inborn preterm infants <32 weeks’ gestation admitted to a tertiary NICU (January 2022–December 2024). Axillary temperatures were obtained after stabilization in the delivery room (DR) and again on NICU admission. Hypothermia was defined as <36.5 °C; infants were grouped by thermal status at each time point. Outcomes were in-hospital mortality and major morbidities. Associations were evaluated with multivariable logistic regression: morbidity models adjusted for gestational age, and mortality models adjusted for gestational age, major intraventricular hemorrhage (IVH), and sepsis; results are reported as adjusted odds ratios with 95% CIs.ResultsHypothermia occurred in 19% of infants in the DR and in 25% at NICU admission. The median temperature change between the DR and NICU was −0.1 °C [IQR: −0.2, 0.1], with a significant overall decline (p = 0.002). Mortality was higher in infants who were hypothermic in the DR (26.3% vs. 7.2%, p < 0.001) and at NICU admission (22.4% vs. 7.1%, p < 0.001). NICU hypothermia was independently associated with bronchopulmonary dysplasia (aOR: 1.89; 95% CI: 1.06–3.35), major IVH (aOR: 2.46; 95% CI: 1.05–5.75), and surgical necrotizing enterocolitis (aOR: 4.89; 95% CI: 1.48–16.17). Delivery-room hypothermia was associated with increased odds of BPD (aOR: 1.88; 95% CI: 1.02–3.46) but not with IVH or NEC. Infants hypothermic at both time points had the highest rates of mortality (25.9%) and BPD (59%).ConclusionHypothermia in the DR and at NICU admission is significantly associated with adverse outcomes, with the highest risk in infants hypothermic at both time points. These observational findings should be interpreted in light of potential selection bias, as smaller and sicker infants are more likely to be hypothermic, and highlight the need to prioritize thermoregulation from birth through admission.